GAGELARAN DALANG MANUT DHARMA PAWAYANGAN PUPPETEER’S DUTY ACCORDING ANCIENT WISDOM DHARMA PAWAYANGAN - I Gusti Putu Sudarta (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Dharma Pawayangan is a palm leaf manuscript containing instructions about a puppeteer's obligations (dharma). The text must be understood and carried out by a puppeteer in fulfilling his obligations to remain consistent with Hindu ethics and spirituality. Before a candidate for the puppeteer studies Dharma Pawayangan, the first step must be to know about self-essence, wandering into himself to realize and exceed the layers of body consciousness, mind, emotions, and intelligence so that it reaches Budhi's consciousness. Examining and discussing the text of Dharma Pawayangan to formulate the question that leads to what exactly is the capacity of the puppeteer (gagelaran dalang)? In dissecting this question, the aesthetic theory is used and supported by hermeneutics theory. The result obtained is that the puppeteers’ capacities following the text of Dharma Pawayangan is the Ucap-ucap Tatwa Carita. Ucap-ucap means that the empowerment of vocal puppeteers, which includes the entire voice and developing techniques, understanding of the organs that produce sound, sound processing, breathing and prana techniques, script (aksara) as a symbol of sound (swara), and aware of the vibration of the universe, namely Nada Brahma. Tatwa is a philosophy and spiritual; the puppeteer must master philosophy, yoga, and spirituality. In comparison, Carita is to understand the epic Ramayana, Mahabharata, and Bodha Carita well.